Evaluación para la síntesis de una película polimérica derivada de cáscaras de naranja con aceites esenciales antimicrobianos para el control de Rhizopus Stolonifer (2020)
In this research, the synthesis of an active film from lignocellulosic residues from valence orange peels with encapsulation of functional antimicrobial compounds such as essential oils of Thymus vulgaris and Syzygium aromaticum is evaluated for the control of Rhizopus Stolonifer, which causes soft rot of fruits and vegetables. To produce thin films with appropriate mechanical and barrier characteristics, a wet process called “casting” is used. Initially, some preliminary experiments are carried out to determine the forming compounds of the film-forming solution and their inclusion percentage, culminating with a basic formulation of 10% agro-industrial waste (RAI), 8% emulsifier, 5% plasticizer, 2% crosslinker and 75% solvent. The material formulated from the base composition has within its matrix structure an encapsulation of 500 ppm of essential oil of thyme (T01), 500 ppm of essential oil of cloves (C01), 500 ppm in equimal equivalent of essential oil of thyme and clove (M01) and a blank formulation (B01); all of them synthesized by replication and characterized according to current standards for plastic films.